FOREIGN EXPERIENCE OF SOCIAL AND PSYCHOLOGICAL ASSISTANCE TO WOMEN VICTIMS OF DOMESTIC VIOLENCE - Akymbek, G (Журнал Педагогики и психологии в современном образовании, 2024)
The most dangerous traumatic factors in the modern world include various forms of violence that directly threaten the life and health of a person himself and those close to him. According to various studies, it was found that the incidence of mental disorders in people who survived childhood sexual abuse is about 4 times higher than in the general population, the rate is twice as high among men [1] and women who have experienced multiple sexual and physically abused are 20 times more likely to engage in suicidal behavior in difficult life situations than the general population